A Modified Suture Technique for Attaching Radiotransmitters to Northern Bobwhite Chicks. (10th March 2020) - Terhune, Theron M.; Caudill, Danny; Terhune, V. Heather; Martin, James A.
ABSTRACT: Reliable and unbiased information is needed for informing management decisions relevant to all animal life stages. Radiomarking is commonly used for adult birds, but this approach is more challenging for galliform chicks. Following preliminary experimentation of multiple attachment methods, we selected 2 radiotransmitter attachment techniques, gluing and suturing, to test on 11‐day‐old northern bobwhite ( Colinus virginianus ; hereafter, bobwhite) chicks in an outdoor aviary environment during 1 May 2013 through 30 Sep 2016. In addition, we field‐tested a novel, modified‐suture technique on 11‐ and 12‐day‐old wild bobwhite chicks. We found that suturing was a superior method of transmitter attachment. Glue‐on attachment of transmitters performed poorly with average retention rates <7 days. The probability of retaining a radiotransmitter for the duration of our 8‐week study was 0.76 (±0.08 SE), 0.89 (±0.09 SE), and 0.00 for normal suture, our modified suture, and glue‐on techniques, respectively. Development and growth of suture‐ and patagial‐tagged bobwhite chicks (average mass gain of 41.95 g ± 2.79 SE) was unimpeded compared with a control (patagial‐tagged only, no transmitter) group of birds (average mass gain: 40.89 g ± 2.91 SE). We observed similar tag‐retention rates (0.906 ± 0.07 SE) of transmitters affixed to wild bobwhite chicks in the field using a modified‐suture technique compared with the aviary study. Our modifications to the traditional suture methods include changing the placement of the transmitter to reduce snag rate in vegetation, using a smaller gauge syringe needle to reduce skin‐tearing, applying a surgeon's knot for increased knot‐security and reduced knot slippage while suturing, and applying insta‐set spray to rapidly dry superglue to reduce handling time of chicks. The modified‐suture technique provides improvements in tag‐retention, facilitates shorter handling time of birds in the field, and provides an effective means for tagging and tracking individuals to collect ecological data and demographic vital rates on bobwhite chicks and other birds. Future studies should investigate potential sublethal effects that suture tags may impose on individuals to identify and account for estimable biases of vital rates. © 2020 The Wildlife Society. Abstract : Limited data exist on game birds with precocial young because of the difficulty of capturing and tagging small, rapidly growing chicks with miniature tracking devices. The modified suture technique we have developed provides a technique for quickly and reliably affixing miniature radiotags to bobwhite chicks, affording a new window of opportunity into their ecology.